ApoA-I mimetic does not improve left ventricular diastolic dysfunction in rabbits without aortic valve stenosis. (15th May 2021) - Nachar, Walid; Merlet, Nolwenn; Maafi, Foued; Mihalache-Avram, Teodora; Mecteau, Mélanie; Gélinas, Danielle; Shi, Yanfen; Brodeur, Mathieu; Alem, Sonia; Blondeau, Lucie; Cossette, Mariève; Guertin, Marie-Claude; et al.
Abstract: Background: We previously demonstrated that high-density lipoprotein (HDL) infusions may improve left ventricular diastolic dysfunction (LVDD) in an aortic valve stenosis (AVS) model. Whether the benefit was direct or mediated by the observed reduction in AVS severity is not clear. Here, we aimed to test the direct effect of an ApoA-I mimetic on LVDD in the absence of AVS. Methods: Rabbits were exposed to three different protocols to develop LVDD. First, rabbits were exposed to 0.5% cholesterol-rich diet for an average of 17 weeks. Second, rabbits were subjected to surgical ascending aortic constriction (AAC), to mimic the effect of fixed reduced aortic valve area, and studied after 10 weeks. The third model combined both cholesterol-enriched diet (for 12 weeks) and surgical AAC. The control group consisted of age-matched rabbits under normal diet. After development of LVDD, rabbits were randomized to receive infusions of saline or apoA-I mimetic (25 mg/kg) 3 times per week for 4 weeks. Detailed cardiac structure and function measurements were assessed at baseline and weekly during treatment period. Histological and molecular analyses were performed on LV samples. Results: In the three models, echocardiographic results showed development of LVDD over time, with preserved LV systolic and aortic valve functions versus controls. ApoA-I mimetic infusions did not significantly improve echocardiographic parameters nor molecular markers of cardiac inflammation, oxidative stress and fibrosis. Conclusion: ApoA-I mimetic therapy did not directly improve LVDD. These results indicate that previously observed changes of LVDD were caused by AVS improvement induced by this treatment. Highlights: ApoA-I mimetic infusions have no direct beneficial effect on diastolic dysfunction. 3 different rabbit models were used to test the effects of ApoA-I mimetic on diastolic dysfunction. Cardiac diastolic dysfunction was assessed by echography and molecular analysis.